2023
DOI: 10.1136/archdischild-2022-324884
|View full text |Cite
|
Sign up to set email alerts
|

Effects of size at birth on health, growth and developmental outcomes in children up to age 18: an umbrella review

Abstract: BackgroundSize at birth, an indicator of intrauterine growth, has been studied extensively in relation to subsequent health, growth and developmental outcomes. Our umbrella review synthesises evidence from systematic reviews and meta-analyses on the effects of size at birth on subsequent health, growth and development in children and adolescents up to age 18, and identifies gaps.MethodsWe searched five databases from inception to mid-July 2021 to identify eligible systematic reviews and meta-analyses. For each… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 200 publications
0
2
0
Order By: Relevance
“…The evolution analysis of BMI percentiles and/or z-score in the study of sample populations, according to the gestational age, is important to analyze whether the 50 percentile (median) and the 10 and 90 percentiles, usually used to assess the intrauterine growth of newborns, show a trend like the one observed for the newborn group as a whole 20,27,28 .…”
Section: Discussionmentioning
confidence: 99%
“…The evolution analysis of BMI percentiles and/or z-score in the study of sample populations, according to the gestational age, is important to analyze whether the 50 percentile (median) and the 10 and 90 percentiles, usually used to assess the intrauterine growth of newborns, show a trend like the one observed for the newborn group as a whole 20,27,28 .…”
Section: Discussionmentioning
confidence: 99%
“…Since exposures, disease patterns, policies, and health systems differ by setting, our longitudinal dataset will provide new possibilities to study a wide spectrum of policy-relevant questions that apply to urban-poor populations. For example, a 2023 review found that most studies examining the effect of size at birth on subsequent child wellbeing outcomes have been in high-income countries [ 20 ] or have not considered size for gestational age; such analyses are possible in our birth cohort. Another unusual feature of our cohort is that it includes five settings and services clustered in 140 health facilities and 702 schools, allowing for context-specific and comparative questions.…”
Section: Discussionmentioning
confidence: 99%
“…A respeito do comprimento, trata-se do indicador de crescimento que melhor refletiria a massa magra e estaria menos sujeito à influência de fatores externos como, por exemplo, o ambiente intrauterino (JAMALUDDINE Z et.al, 2023;YOON SJ et.al, 2021;BLAIR EM et al, 2005). Cabe salientar que, para a tomada de ambas as medidas, é necessário contar com uma equipe suficientemente treinada, de maneira a preservar a acurácia dos valores mensurados (SBP, 2017).…”
Section: Lista De Siglasunclassified